2013
DOI: 10.1063/1.4823815
|View full text |Cite
|
Sign up to set email alerts
|

Accurate argon cluster-ion sputter yields: Measured yields and effect of the sputter threshold in practical depth-profiling by x-ray photoelectron spectroscopy and secondary ion mass spectrometry

Abstract: Newcastle University ePrintsCumpson PJ, Portoles JF, Barlow AJ, Sano N. Accurate argon cluster-ion sputter yields: Measured yields and effect of the sputter threshold in practical depth-profiling by x-ray photoelectron spectroscopy and secondary ion mass spectrometry.Argon Gas Cluster-Ion Beam sources are likely to become widely used on x-ray photoelectron spectroscopy and secondary ion mass spectrometry instruments in the next few years. At typical energies used for sputter depth profiling the average argon a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 34 publications
4
43
0
Order By: Relevance
“…10). Similarly, the physical sputter yield data of SiO 2 for Ar + ion bombardment 95,122,124,128,[133][134][135][136][137] show significant scatter (see Fig. 11).…”
Section: Issues and Needsmentioning
confidence: 99%
“…10). Similarly, the physical sputter yield data of SiO 2 for Ar + ion bombardment 95,122,124,128,[133][134][135][136][137] show significant scatter (see Fig. 11).…”
Section: Issues and Needsmentioning
confidence: 99%
“…When we consider the following three important corrosion products of Zn and Zn-alloy coated steel -hydrozincite, simonkolleite and zinc hydroxide -ion etching may at first lead to the erroneous assumption of the appearance or enrichment of zinc oxide at depth. In relation to developments in sputter equipment, it is notable that, in addition to Ar cluster guns [9], sources of buckminsterfullerene clusters [33] have been available for some time. We anticipate that oxygen cluster guns will soon be used in common commercial setups, where they may provide higher sputter rates than argon clusters for inorganic compounds.…”
Section: Ar Cluster Sputtering On Feomentioning
confidence: 99%
“…The present work focused on Fe(II) oxide and hydrozincite as two representative corrosion products that are susceptible to degradation. Furthermore, the potential of newer and more sophisticated sputter systems such as cluster guns [8,9] was tested using both materials, since the operation of such devices (e.g., providing Ar clusters and buckminsterfullerene C 60 clusters) has already shown promising results in other fields [7,10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…2. Note also that a recent investigation by Cumpson et al identified several polymers with significantly lower sputter yields than PC upon 4 keV Ar 1000 bombardment, such as poly(ethylene terephthalate) and polyether ether ketone, which are both semicrystalline polymers [51]. The experimental sputtering yields of inorganic materials such as Si, SiO 2 and Au were also compiled by Seah in [49].…”
Section: Projectile Penetration Cratering and Sputteringmentioning
confidence: 95%